0054 Metacognition and patient safety. (2nd November 2015) - Walsh, Ian; Spence, Andrew; Murray, James
Abstract : Background/context: Clinical decision making is a unique process employing knowledge of pathological conditions, explicit patient information and experiential learning. 1 With increasing emphasis on evidence-based practice, a multidimensional approach to decision making combines information processing and patient-specific elements which may provide clinical cue and pattern recognition. 1, 2 Cognitive reflective testing is an accurate method for predicting performance and is designed to measure the tendency to override immediate, intuitive (yet incorrect) responses. 3 Awareness of cognitive reflective processes may improve performance and decision making. 4 We aimed to determine if cognitive reflection exerts a positive influence on clinical decision making in undergraduate medical students. Methodology: 153 final year undergraduate medical students completed an interactive Safe Thinking Workshop on nontechnical skills and patient safety, incorporating basic metacognitive concepts. All students participated in cognitive reflective testing during the workshop. The students were then asked to manage a simulated clinical case (acute respiratory distress), including biochemical diagnosis, clinical diagnosis and effective management. A separate inquiry was to determine if students could gauge respiratory distress severity. The study group (n = 78) completed the clinical scenario immediately after the workshop, whilst the control group (n = 75) completed the scenario beforehand. Outcomes: The mean total score for study students was 80.5%, with a score of 57.9% for the control group (t-test; p < 0.05). Classification of illness severity was correct in 13.2% of study students and 4.1% of control students (p < 0.05). Conclusion and recommendations: These results suggest that clinical decision making and recognition of illness severity may be enhanced by specific teaching in nontechnical skills, metacognitiion and cognitive reflection. Potential impact/take home message: In a simulated environment, awareness of cognitive shortfalls and implementation of techniques to improve cognition may enhance clinical decision making and safe practice. References: Banning M. A review of clinical decision making: models and current research. J Clin Nurs 2008;17(2):187–95 Saltman D, Jackson D, Newton PJ, Davidson PM. In pursuit of certainty: can the systematic review process deliver? BMC Med Inform Decis Mak 2013;13:25 Topiak ME, West RF, Stanovich KE. The cognitive reflection test as a predictor of performance on heuristics-and-biases tasks. Mem Cogn 2011;39:275–89 Frederick S. Cognitive reflection and decision making. J Econ Perspect 2005;19(4):25–42